Deferoxamine Alleviates Osteoarthritis by Inhibiting Chondrocyte Ferroptosis and Activating the Nrf2 Pathway - Guo, Zhou; Lin, Jiamin; Sun, Kai; Guo, Jiayou; Yao, Xudong; Wang, Genchun; Hou, Liangcai; Xu, Jingting; Guo, Jiachao; Guo, Fengjing (Frontiers in Pharmacology, 2022)
Objective: Osteoarthritis (OA) is a common disease with a complex pathology including mechanical load, inflammation and metabolic factors. Chondrocyte ferroptosis contributes to OA progression. Since iron deposition is a major pathological event in ferroptosis, deferoxamine (DFO), an effective iron chelator, has been used to inhibit ferroptosis in various degenerative disease models. Nevertheless, its OA treatment efficacy remains unknown. We aimed to determine whether DFO improves chondrocyte ferroptosis and its effect on OA and to explore its possible mechanism. Methods: IL-1β was used to simulate inflammation, and chondrocyte ferroptosis was induced by erastin, a classic ferroptosis inducer. A surgical destabilized medial meniscus (DMM) mouse model was also applied to simulate OA in vivo, and erastin was injected into the articular cavity to induce mouse knee chondrocyte ferroptosis. We determined the effects of DFO on ferroptosis and injury-related events: chondrocyte inflammation, extracellular matrix (ECM) degradation, oxidative stress and articular cartilage degradation. Results: IL-1β increased the levels of ROS, lipid ROS, and the lipid peroxidation end product malondialdehyde (MDA) and altered ferroptosis-related protein expression in chondrocytes. Moreover, ferrostatin-1 (Fer-1), a classic ferroptosis inhibitor, rescued the IL-1β-induced decrease in collagen type II (collagen II) expression and increase in matrix metalloproteinase 13 (MMP13) expression. Erastin promoted MMP13 expression in chondrocytes but inhibited collagen II expression. DFO alleviated IL-1β- and erastin-induced cytotoxicity in chondrocytes, abrogated ROS and lipid ROS accumulation and the increase in MDA, improved OA-like changes in chondrocytes, and promoted Nrf2 antioxidant system activation. Finally, intra-articular injection of DFO enhanced collagen II expression in OA model mice, inhibited erastin-induced articular chondrocyte death, and delayed articular cartilage degradation and OA progression. Conclusion: Our research confirms that ferroptosis occurs in chondrocytes under inflammatory conditions, and inhibition of chondrocyte ferroptosis can alleviate chondrocyte destruction. Erastin-induced chondrocyte ferroptosis can stimulate increased MMP13 expression and decreased collagen II expression in chondrocytes. DFO can suppress chondrocyte ferroptosis and promote activation of the Nrf2 antioxidant system, which is essential for protecting chondrocytes. Additionally, ferroptosis inhibition by DFO injection into the articular cavity may be a new OA treatment.